Wspomnienie o Jerzym Jarzębskim - Juszczyk, Andrzej (Przestrzenie Teorii, 2024)
On 25 February 2024, at the age of 76, Prof. Jerzy Jarzębski, an outstanding expert on Polish literature, an excellent literary critic, professor at the Faculty of Polish Studies of the Jagiellonian University, died in Warsaw.